2021
DOI: 10.1007/s40031-021-00623-4
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of COVID 19 Cases in Karnataka State using Artificial Neural Network (ANN)

Abstract: COVID-19 is a pandemic that has caused lot of deaths and infections in the last 2 months and is showing an increasing trend not only in the number of infections and deaths, but also in the recovery rate. Accurate prediction models are very much essential to make proper forecasts and take necessary actions. This study demonstrates the capability of Multilayer Perceptron (MLP), an Artificial Neural network (ANN) model for forecasting the number of infected cases in the state of Karnataka in India. It is trained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…In general, the multivariate LSTM model significantly outperformed the other models, displaying an average improvement of 61 – 71 % in the MAPE compared to the univariate models ( Table 4 ). The improvement is similar to a study done by Shetty and Pai, (2021) who observed a 66% improvement in the MAPE (from 20.73% to 7.03%) after implementing a cookoo search algorithm for better forecasting of COVID-19 cases in the state of Karnataka, India.…”
Section: Resultssupporting
confidence: 88%
“…In general, the multivariate LSTM model significantly outperformed the other models, displaying an average improvement of 61 – 71 % in the MAPE compared to the univariate models ( Table 4 ). The improvement is similar to a study done by Shetty and Pai, (2021) who observed a 66% improvement in the MAPE (from 20.73% to 7.03%) after implementing a cookoo search algorithm for better forecasting of COVID-19 cases in the state of Karnataka, India.…”
Section: Resultssupporting
confidence: 88%
“…They demonstrated that LSTM model performed better in the medium and long range forecasting scale when integrated with the weather data. Shetty [63] presented real-time forecasting using a simple neural network for the COVID-19 cases in the state of Karnataka in India where parameter selection for the model was based on cuckoo search algorithm. The study reported that the mean-absolute percentage error (MAPE) was reduced from 20.73% to 7.03% and the proposed model was further tested on the Hungary COVID-19 dataset and reported promising results.…”
Section: Modelling and Forecasting Covid-19mentioning
confidence: 99%
“…Among the machine-learning techniques, ANN-based methods have exhibited superiority over other methods in forecasting COVID-19 cases ( Shetty and Pai, 2021 ). ANNs were developed based on the mechanisms of biological nerve systems ( Maind et al., 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Feed-forward neural networks and the MLP are forms of ANNs that have been used to forecast the spread rate of COVID-19 in India ( Chakraborty, Choudhary, Sarma, Hazarika, 2020 , Shetty, Pai, 2021 ) and across the continental USA ( Mollalo et al., 2020 ). Rizk-Allah and Hassanien (2020) presented a hybrid forecasting model that combines a multi-layer feed-forward neural network with an interior search algorithm to forecast the spread of COVID-19 in the USA, Italy, and Spain.…”
Section: Literature Reviewmentioning
confidence: 99%